ANALISIS KELAYAKAN FINANSIAL USAHA PENYULINGAN MINYAK DAUN CENGKEH DI DESA LUMBU TAROMBO KECAMATAN BANAWA SELATANKABUPATEN DONGGALA - Mita Mita; M.R Yantu; sulaeman sulaeman (Agroland: Jurnal Ilmu-ilmu Pertanian, 2013)
The aim of the research was to analyze the financial feasibility of clove leaf oil refining business in Lumbu Tarombo Village, Banawa Sub District, Donggala District. The research location was purposively determined. The respondents who purposively selected were those directly involved in business including leaders and workers. Primary and secondary data collected were analyzed using financial feasibility methods including Net Present Value (NPV), Net Benefit Cost Rasio (Net B/C), Internal Rate of Return (IRR), Payback Period (PP), Sensitivity tool analyses. The calculation of financial feasibility criteria in the clove leaf oil refining business showed that NPV during the period of 2012 – 2014 was IDR 59,848,649 with Net B/C was 2 resulting in IRR of 44% and PP for 5 months. Sensitivity analysis indicated that with raising the price and variable cost for 5%, the business of the clove leaf oil refining is feasible to be developed. Key Words : Financial feasibility, Internal Rate of Return, Net Benefit Cost Ratio, Net Present Value, and Payback Period.